Evaluating logistics suppliers in the Slovenian market - Završnik, Bruno (Organizacija (Kranj), 2007)
This paper focuses on logistics performance of companies in the Slovenian market. The research is analysing the point of view of managers in production, trade and services oriented companies about their logistics needs. Specifically, we examined their perception of different characteristics of a logistics provider and their evaluation in the process of outsourcing. There are few logistics functions that have been outsourced. This paper presents the outsourcing process with of outsourcing characteristics. The authors also identify elements of a successful outsourcing strategy, basing their conclusions on the research on the sample of 150 the biggest Slovenian companies. The authors will intend to answer the following question in the research: Which indicators do customers use to evaluate their suppliers? It would be expected that in purchase decision processes, customers give strong consideration to the resources and the competence of the supplier as criteria to provide higher quality and more reliable and efficient transportation of goods. One of the aims of research will be to measure the perception of respondents about the different characteristics of logistics provider. Within any organization, there will be differences of opinion about key buying factors, their importance, and how well the company performs on each factor.
Keywords: podjetja; storitve; logistika; preskrba; vrednotenje